Logic structure of scientific theories: syntactic and semantic view - Gallardo Corrales, Andrés (2021)
The paper summarizes the main characterizations of scientific theories, as described by the so-called “syntactic” and “semantic” traditions. Each of these perspectives identifies a logic structure of a theory. The syntactic tradition equates scientific theories with a not-interpreted formal system, that can be expressed in first order logic. In the other hand, the semantic view makes an axiomatization of theories by the definition of set-theoretical predicates, using intuitive set theory. In the first perspective it is possible to highlight the predictive elements of scientific theories, while the second approach has the advantage of incorporating historical and intertheoretical elements in its formalism.